PENERAPAN METODE AS-SAM’IYYAH ASY-SYAFAWIYAH UNTUK MENINGKATKAN KEMAMPUAN BERBICARA DAN MENULIS TEKS SEDERHANA BAHASA ARAB - Dian Ardiana (DIADIK, 2024)
The objectives of this study are to: (1) describe the application of the As-Sam'iyyah Asy-Syafawiyah Method to improve Arabic speaking skills in Arabic lessons. (2) Describe the application of the As-Sam'iyyah Asy-Syafawiyah Method to improve the ability to write simple Arabic texts in Arabic lessons and (3) Describe the effectiveness of the As-Sam'iyyah Asy-Syafawiyah method in improving the ability to speak and write simple texts Arabic class XII MIPA SMA N 4 Lahat. In this study, the Classroom Action Research (CAR) method was used and experimental. The subjects of this study were students of class XII MIPA at SMAN 4 Lahat. Data collection techniques used observation sheets and student test methods. Analysis of the data used values ​​are (1) Pre-test and Post-test analysis, (2) t-test analysis of the ability to speak and write simple Arabic texts. The conclusions of this research are; The application of the As-Sam'iyyah Asy-Syafawiyah learning method is effective in improving students' speaking and writing skills in simple Arabic texts compared to with conventional learning models